Preparation method of ZnO varistor for improving high-current impact stability
By pre-synthesis and doping with Bi2O3 and TiO2 at 825 °C in the ZnO varistor chip, the generation ratio of Bi2O3 phase is adjusted, and the problem of insufficient stability under large current impact is solved, and the voltage is realized The rate of change of the acoustic voltage is significantly reduced and the resistance stability is improved.
Patent Information
- Application Number
- CN202411626551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ZnO varistor chips are insufficient in stability under large current impact, and the varistor voltage change rate is large, which affects the overvoltage protection performance of the lightning arrester.
By pre-synthesis with Bi2O3 at 825°C, combined with TiO2 doping, the generation ratio of Bi2O3 phase is adjusted, the generation of γ-Bi2O3 phase is increased, the grain boundary barrier is improved, and the resistance stability is improved.
The varistor rate of change of the ZnO varistor chip after a large current impact is significantly reduced, from 5% to 1.5%, improving the stability of the resistance and improving the square wave pass rate by 2%.
Smart Images

Figure CN119430906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ZnO varistor sheet, and in particular to a method for preparing a ZnO varistor sheet with high current impact stability. Background Art
[0002] In recent years, people's living standards have gradually improved, and the total electricity consumption in my country has also increased year by year. The power transmission and distribution network has been continuously expanded, but power accidents have been greatly reduced, and people's electricity safety has been better guaranteed. Zinc oxide lightning arresters play an important role in this. Zinc oxide lightning arresters have good application prospects in overvoltage protection because of their good nonlinear volt-ampere characteristics. The nonlinear volt-ampere characteristics of the lightning arrester come from its core component, zinc oxide varistor, and the development of zinc oxide varistor is developed with the requirements of lightning arresters. Zinc oxide lightning arresters still need to continue to operate on the line after being struck by lightning, so it is necessary to ensure that the zinc oxide lightning arrester has a large current capacity and a small varistor voltage change rate. ZnO varistor is a polycrystalline ceramic material sintered by ceramic technology with ZnO as the main body and a variety of metal oxides (Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, etc.). Its current-voltage (IV) characteristics are similar to those of a bidirectional Zener diode and have good nonlinearity. As a polycrystalline ceramic material, the internal microstructure of ZnO varistor is composed of ZnO grains and grain boundary layers between different grains. Various doping elements form limited solid solutions with ZnO grains due to their differences in ion radius and electronegativity. 3+ The ionic radius (1.03Å) is smaller than that of Zn 2+ The ionic radius (0.74Å) is large, and the difference between Bi electronegativity (2.02) and Zn electronegativity (1.65) is large. During the sintering process, it will not dissolve in the ZnO grains, but segregate at the grain boundary to form a Bi-rich thin layer, produce surface states, and thus form a grain boundary barrier to produce nonlinearity. Bi2O3 melts into a liquid phase at 825 ℃, promoting ZnO sintering, grain growth, solid solution of additives and ZnO, and segregation of some additives in the grain boundary layer during cooling, which plays a very important role in improving the grain boundary barrier. In addition, the three-dimensional network structure formed by Bi2O3 during the sintering process is conducive to the diffusion and accumulation of oxygen in the grain boundary layer. Excess oxygen in the grain boundary layer will form acceptor energy levels, which helps to improve the grain boundary barrier.
[0003] Bi2O3 mainly exists in four crystal forms: α, β, γ and δ. When sintered at high temperature, the generated Bi2O3 mainly exists in the δ phase, which has a large ion mobility, which is conducive to grain growth and uniform distribution of additive ions in the varistor ceramics. When sintered and cooled, δ-Bi2O3 transforms into β-Bi2O3, γ-Bi2O3 and α-Bi2O3, among which δ-Bi2O3 and β-Bi2O3 have larger ion mobility than γ-Bi2O3 and α-Bi2O3 phases. In order to make the varistor have better stability when withstanding overvoltage, a lower ion mobility is required to prevent the change of grain boundary barrier caused by the diffusion loss of oxygen in the grain boundary layer. Therefore, the generation ratio of β-Bi2O3, α-Bi2O3 and γ-Bi2O3 in the varistor has a great influence on the stability of the varistor.
[0004] A method for preparing a ZnO varistor sheet with high current impact stability is provided to solve the above technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a ZnO varistor sheet with high current impact stability, by pre-synthesizing with Bi2O3 at 825°C and then doping, so as to improve the high current impact stability of the varistor.
[0006] The object of the present invention is achieved in that: A method for preparing a ZnO varistor sheet with improved high current impact stability, wherein the raw materials for preparing the ZnO varistor sheet are configured in molar percentage: ZnO 90-97%, Bi2O3 0.5-2.0%, Sb2O3 0.5-2.0%, Co2O3 0.1-1.5.0%, MnO2 0.1-1.0%, NiO 0.1-1.0%, Cr2O3 0.1-1.0%, A12O3 0.01-0.5% and TiO2 0.05-1.0%; A method for preparing a ZnO varistor sheet with improved high current impact stability comprises the following steps: S1: Bi2O30.5-2.0% and TiO20.05-1.0% are mixed evenly and calcined at 825 ℃ for 6 h. After calcination, the materials are crushed, and the crushed pre-synthesized product Bi-Ti-O is mixed with ZnO90-97%, Sb2O30.5-2.0%, Co2O30.1-1.5.0%, MnO20.1-1.0%, NiO0.1-1.0%, Cr2O30.1-1.0% and A12O30.01-0.5% to obtain a mixed material; S2: The mixed material in step S1 is mixed with deionized water and then ball-milled for 12-24 h at a ball-milling speed of 100-200 r / min. During the ball-milling process, a dispersant (tetradecyl ammonium acetate), a defoaming agent (polymer of ethylene oxide and propylene oxide) and a binder (PVA) need to be added to obtain a mixed slurry; S3: drying the mixed slurry of step S2 at 100-120°C for 12 h, crushing the mixed slurry and passing it through a 100-mesh sieve to obtain powder 1; S4: the powder material 1 of step S3 is mixed evenly with a lubricant (glycerol) and deionized water and then aged for 12 hours to obtain a powder material 2; S5: forming the powder 2 of step S4 into a cake-shaped resistor sheet under a pressure of 10-20 MPa; S6: pre-calcining the resistor chip body of step S5 at 300-500° C. for 2-4 h, performing a debinding treatment to remove the dispersant, defoaming agent and adhesive, and obtaining a resistor chip intermediate 1; S7: pre-calcining the resistor intermediate 1 of step S6 at 750-900° C. for 1-3 h to obtain a resistor intermediate 2; S8: coating the side of the resistor intermediate 2 in step S7 with an inorganic high-resistance layer and calcining at 1050-1250°C for 2-4h to obtain a resistor intermediate 3, wherein the inorganic high-resistance layer is formed by mixing a mixed powder of ZnO 40%, Bi2O3 20%, Sb2O3 10%, SiO2 30% and a binder PVA in a mass ratio of 1:1; S9: grinding the upper and lower end surfaces of the resistor intermediate 3 in step S8 flat and then heat treating at 500-600° C. for 2-3 hours to obtain a resistor intermediate 4; S10: spraying aluminum electrodes on the upper and lower end surfaces of the intermediate 4 in step S9, and coating the side surfaces with insulating glaze to obtain a finished zinc oxide varistor sheet.
[0007] In step S1, the calcination heating rate is 5-10°C / min; in step S6, the calcination heating rate is 10-20°C / min; in step S7, the calcination heating rate is 20-40°C / min; in step S8, the calcination heating rate is 40-80°C / min; in step S9, the calcination heating rate is 20-30°C / min.
[0008] In the step S2, the particle size D50 of the mixed slurry is 0.3-0.5 μm.
[0009] In step S3, the moisture content of the powder 1 is 0.01-0.15%; in step S4, the moisture content of the powder 2 is 1.0-1.5%.
[0010] In the step S8, the inorganic high-resistance layer is coated with a thickness of 0.1-0.2 mm.
[0011] In the step S9, the flatness of the resistor sheet after grinding is less than 0.1 mm.
[0012] In the step S10, the aluminum electrode is sprayed with a thickness of 0.08-0.15 mm, and the insulating glaze is coated with a thickness of 0.15-0.3 mm.
[0013] The beneficial effects of the present invention are: 1. The present invention increases the generation ratio of γ-Bi2O3 phase by doping TiO2, which helps to reduce the varistor voltage change rate after a large current impact and improve the stability of the ZnO varistor. Furthermore, Bi2O3 and TiO2 are mixed evenly and then calcined at 825°C before doping, which helps TiO2 enter the Bi2O3 phase, further improving the stability of the ZnO varistor and reducing the varistor voltage change rate after a large current impact from 5% to 1.5%.
[0014] 2. Bi2O3 is easy to volatilize due to its low melting point during high-temperature sintering, which will increase the pores inside the varistor, thereby reducing the square wave qualified rate of the ZnO varistor. However, doping with Bi2O3 and TiO2 after calcination at 825°C helps to reduce the volatilization of Bi2O3 and increase the square wave qualified rate of the ZnO varistor by 2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 XRD patterns of ZnO varistor sheets obtained in Examples 1-4 and Comparative Example 1 of the present invention; Figure 1 (a) is the XRD spectrum of the ZnO varistor sheets obtained in Examples 1-4 and Comparative Example 1 at 2ϴ of 5-80°; Figure 1 (b) is an XRD enlarged image of the ZnO varistor sheets obtained in Examples 1-4 and Comparative Example 1 at 2ϴ of 25-28.8°; Figure 2 SEM images of ZnO varistor sheets prepared in Examples 1-4 and Comparative Example 1 of the present invention; Figure 3 The frequency distribution histogram of the grain size of the ZnO varistor sheets obtained in Examples 1-4 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0017] Embodiment 1: The following raw materials were prepared in molar percentage: 96% ZnO, 1.0% Bi2O3, 0.8% Sb2O3, 0.6% Co2O3, 0.5% MnO2, 0.5% NiO, 0.5% Cr2O3, 0.05% A12O3, 0.05% TiO2; the Bi2O3 and TiO2 were mixed evenly, calcined at 825 °C for 6 h, crushed and mixed with ZnO and other additives to obtain a mixed material. The mixed material was mixed with deionized water and ball milled for 12 h at a ball milling speed of 200 r / min. Dispersants, defoamers and adhesives were added during the ball milling process to obtain a mixed slurry. The mixed slurry was dried at 100 °C for 12 h, crushed and passed through a 100-mesh sieve to obtain powder 1. The powder 1 was mixed evenly with a lubricant and deionized water and aged for 12 h to obtain powder 2. The powder 2 is formed into a cake-shaped resistor sheet blank under a pressure of 20 MPa. The resistor sheet blank is pre-calcined at 300-500 ° C for 2 h, and subjected to a debinding treatment to remove organic substances such as dispersants, defoamers and adhesives to obtain a resistor sheet intermediate 1. The resistor sheet intermediate 1 is pre-calcined at 750-900 ° C for 1 h to obtain a resistor sheet intermediate 2. The side of the resistor sheet intermediate 2 is coated with an inorganic high-resistance layer and then calcined at 1050-1250 ° C for 2 h to obtain a resistor sheet intermediate 3. The upper and lower end surfaces of the resistor sheet intermediate 3 are ground and flattened and then heat-treated at 500 ° C for 2 h to obtain a resistor sheet intermediate 4. Aluminum electrodes are sprayed on the upper and lower end surfaces of the intermediate 4, and insulating glaze is coated on the side to obtain a finished zinc oxide varistor sheet.
[0018] Example 2: The following raw materials are prepared in molar percentage: 95.7% ZnO, 1.0% Bi2O3, 0.8% Sb2O3, 0.6% Co2O3, 0.5% MnO2, 0.5% NiO, 0.5% Cr2O3, 0.05% A12O3, 0.3% TiO2; the above Bi2O3 and TiO2 are mixed evenly, calcined at 825 °C for 6 h, crushed and mixed with ZnO and other additives to obtain a mixed material. The above mixed material is mixed with deionized water and ball milled for 18 h, with a ball milling speed of 150 r / min. Dispersants, defoamers and adhesives need to be added during the ball milling process to obtain a mixed slurry. The above mixed slurry is dried at 100 °C for 12 h, crushed and passed through a 100 mesh screen to obtain powder 1. The above powder 1 is mixed evenly with a lubricant and deionized water and aged for 12 h to obtain powder 2. The powder 2 is formed into a cake-shaped resistor sheet blank under a pressure of 15 MPa. The resistor sheet blank is pre-calcined at 300-500 ° C for 3 h, and subjected to a debinding treatment to remove organic substances such as dispersants, defoamers and adhesives to obtain a resistor sheet intermediate 1. The resistor sheet intermediate 1 is pre-calcined at 750-900 ° C for 2 h to obtain a resistor sheet intermediate 2. The side of the resistor sheet intermediate 2 is coated with an inorganic high-resistance layer and then calcined at 1050-1250 ° C for 3 h to obtain a resistor sheet intermediate 3. The upper and lower end surfaces of the resistor sheet intermediate 3 are ground and flattened and then heat-treated at 500 ° C for 2.5 h to obtain a resistor sheet intermediate 4. Aluminum electrodes are sprayed on the upper and lower end surfaces of the intermediate 4, and insulating glaze is coated on the side to obtain a finished zinc oxide varistor sheet.
[0019] Example 3: The following raw materials are prepared in molar percentage: 95.4% ZnO, 1.0% Bi2O3, 0.8% Sb2O3, 0.6% Co2O3, 0.5% MnO2, 0.5% NiO, 0.5% Cr2O3, 0.05% A12O3, 0.6% TiO2; the Bi2O3 and TiO2 are mixed evenly, calcined at 825 °C for 6 h, crushed and mixed with ZnO and other additives to obtain a mixed material. The mixed material is mixed with deionized water and ball milled for 20 h at a ball milling speed of 120 r / min. Dispersants, defoamers and adhesives need to be added during the ball milling process to obtain a mixed slurry. The mixed slurry is dried at 100 °C for 12 h, crushed and passed through a 100-mesh sieve to obtain powder 1. The powder 1 is mixed evenly with a lubricant and deionized water and aged for 12 h to obtain powder 2. The powder 2 is formed into a cake-shaped resistor sheet blank under a pressure of 18 MPa. The resistor sheet blank is pre-calcined at 300-500 ° C for 3 h, and subjected to a debinding treatment to remove organic substances such as dispersants, defoamers and adhesives to obtain a resistor sheet intermediate 1. The resistor sheet intermediate 1 is pre-calcined at 750-900 ° C for 2 h to obtain a resistor sheet intermediate 2. The side of the resistor sheet intermediate 2 is coated with an inorganic high-resistance layer and then calcined at 1050-1250 ° C for 3 h to obtain a resistor sheet intermediate 3. The upper and lower end surfaces of the resistor sheet intermediate 3 are ground and flattened and then heat-treated at 500 ° C for 2.5 h to obtain a resistor sheet intermediate 4. Aluminum electrodes are sprayed on the upper and lower end surfaces of the intermediate 4, and insulating glaze is coated on the side to obtain a finished zinc oxide varistor sheet.
[0020] Embodiment 4: The following raw materials were prepared in molar percentage: 95% ZnO, 1.0% Bi2O3, 0.8% Sb2O3, 0.6% Co2O3, 0.5% MnO2, 0.5% NiO, 0.5% Cr2O3, 0.05% A12O3, 1.0% TiO2; the above Bi2O3 and TiO2 were mixed evenly, calcined at 825 °C for 6 h, crushed and mixed with ZnO and other additives to obtain a mixed material. The above mixed material was mixed with deionized water and ball milled for 18 h at a ball milling speed of 150 r / min. Dispersants, defoamers and adhesives were added during the ball milling process to obtain a mixed slurry. The above mixed slurry was dried at 100 °C for 12 h, crushed and passed through a 100-mesh sieve to obtain powder 1. The above powder 1 was mixed evenly with a lubricant and deionized water and aged for 12 h to obtain powder 2. The powder 2 is formed into a cake-shaped resistor sheet blank under a pressure of 20 MPa. The resistor sheet blank is pre-calcined at 300-500 ° C for 4 h, and subjected to a debinding treatment to remove organic substances such as dispersants, defoamers and adhesives to obtain a resistor sheet intermediate 1. The resistor sheet intermediate 1 is pre-calcined at 750-900 ° C for 3 h to obtain a resistor sheet intermediate 2. The side of the resistor sheet intermediate 2 is coated with an inorganic high-resistance layer and then calcined at 1050-1250 ° C for 4 h to obtain a resistor sheet intermediate 3. The upper and lower end surfaces of the resistor sheet intermediate 3 are ground and flattened and then heat-treated at 500 ° C for 3 h to obtain a resistor sheet intermediate 4. Aluminum electrodes are sprayed on the upper and lower end surfaces of the intermediate 4, and insulating glaze is coated on the side to obtain a finished zinc oxide varistor sheet.
[0021] Comparative Example 1: The following raw materials are prepared in molar percentage: 96.05% ZnO, 1.0% Bi2O3, 0.8% Sb2O3, 0.6% Co2O3, 0.5% MnO2, 0.5% NiO, 0.5% Cr2O3, 0.05% A12O3; the above raw materials are mixed with deionized water and ball milled for 12 hours at a ball milling speed of 200 r / min. Dispersants, defoamers and adhesives need to be added during the ball milling process to obtain a mixed slurry. The mixed slurry is dried at 100 ° C for 12 hours, crushed and passed through a 100 mesh sieve to obtain powder 1. The above powder 1 is mixed evenly with a lubricant and deionized water and aged for 12 hours to obtain powder 2. The above powder 2 is formed into a cake-shaped resistor sheet blank under a pressure of 20 MPa. The resistor chip blank is pre-calcined at 300-500 ° C for 3 h, and subjected to a debinding treatment to remove organic substances such as dispersants, defoamers and adhesives to obtain a resistor chip intermediate 1. The resistor chip intermediate 1 is pre-calcined at 750-900 ° C for 2 h to obtain a resistor chip intermediate 2. After the side of the resistor chip intermediate 2 is coated with an inorganic high-resistance layer, it is calcined at 1050-1250 ° C for 3 h to obtain a resistor chip intermediate 3. After the upper and lower end surfaces of the resistor chip intermediate 3 are ground flat, they are heat treated at 500 ° C for 2.5 h to obtain a resistor chip intermediate 4. Aluminum electrodes are sprayed on the upper and lower end surfaces of the intermediate 4, and insulating glaze is coated on the side to obtain a finished zinc oxide varistor chip.
[0022] Table 1 is a comparison result of the electrical performance parameters of the ZnO varistor sheets prepared in Examples 1-4 and Comparative Example 1.
[0023] Table 1 Conclusion: 1. Pass Figure 1 It can be seen that after Bi2O3 and TiO2 are doped and calcined at 825 °C, Bi2O3 transforms from β phase to γ phase compared with the undoped TiO2 sample.
[0024] 2. By Figure 2 , Figure 3 From Table 1, it can be seen that the surface grain distribution of Bi2O3 and TiO2 doped after calcination at 825 °C is more uniform and the density is better than that of undoped TiO2 samples.
Claims
1. A method for preparing a ZnO varistor sheet with improved high current impact stability, characterized in that: The raw materials for preparing ZnO varistor sheets are configured in molar percentage: ZnO 90-97%, Bi2O3 0.5-2.0%, Sb2O3 0.5-2.0%, Co2O3 0.1-1.5.0%, MnO2 0.1-1.0%, NiO 0.1-1.0%, Cr2O3 0.1-1.0%, SiO2 0.1-1.0%, A12O3 0.01-0.5% and TiO2 0.05-1.0%; A method for preparing a ZnO varistor sheet with improved high current impact stability comprises the following steps: S1: Bi2O30.5-2.0% and TiO20.05-1.0% are mixed evenly and calcined at 825°C for 6 h. After calcination, the materials are crushed, and the crushed pre-synthesized product Bi-Ti-O is mixed with ZnO90-97%, Sb2O30.5-2.0%, Co2O30.1-1.5.0%, MnO20.1-1.0%, NiO0.1-1.0%, Cr2O30.1-1.0% and A12O30.01-0.5% to obtain a mixed material; S2: The mixed material in step S1 is mixed with deionized water and then ball-milled for 12-24 h at a ball-milling speed of 100-200 r / min. During the ball-milling process, a dispersant, a defoaming agent and a binder need to be added to obtain a mixed slurry; S3: drying the mixed slurry of step S2 at 100-120°C for 12 h, crushing the mixed slurry and passing it through a 100-mesh sieve to obtain powder 1; S4: mixing the powder 1 obtained in step S3 with a lubricant and deionized water and aging for 12 hours to obtain powder 2; S5: forming the powder 2 of step S4 into a cake-shaped resistor sheet under a pressure of 10-20 MPa; S6: pre-calcining the resistor chip body of step S5 at 300-500° C. for 2-4 h, performing a debinding treatment to remove the dispersant, defoaming agent and adhesive, and obtaining a resistor chip intermediate 1; S7: pre-calcining the resistor intermediate 1 of step S6 at 750-900° C. for 1-3 h to obtain a resistor intermediate 2; S8: coating the side of the resistor intermediate 2 in step S7 with an inorganic high-resistance layer and calcining at 1050-1250°C for 2-4 hours to obtain a resistor intermediate 3, wherein the inorganic high-resistance layer is formed by mixing a mixed powder of ZnO 40%, Bi2O3 20%, Sb2O3 10%, and SiO2 30% with a binder in a mass ratio of 1:1; S9: grinding the upper and lower end surfaces of the resistor intermediate 3 in step S8 flat and then heat treating at 500-600° C. for 2-3 h to obtain a resistor intermediate 4; S10: spraying aluminum electrodes on the upper and lower end surfaces of the intermediate 4 in step S9, and coating the side surfaces with insulating glaze to obtain a finished zinc oxide varistor sheet.
2. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In step S1, the calcination heating rate is 5-10°C / min; in step S6, the calcination heating rate is 10-20°C / min; in step S7, the calcination heating rate is 20-40°C / min; in step S8, the calcination heating rate is 40-80°C / min; and in step S9, the calcination heating rate is 20-30°C / min.
3. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In the step S2, the particle size D50 of the mixed slurry is 0.3-0.5 μm.
4. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In step S3, the moisture content of the powder 1 is 0.01-0.15%; in step S4, the moisture content of the powder 2 is 1.0-1.5%.
5. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In the step S8, the inorganic high-resistance layer is coated with a thickness of 0.1-0.2 mm.
6. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In the step S9, the flatness of the resistor sheet after grinding is less than 0.1 mm.
7. The method for preparing a ZnO varistor sheet with improved high current impact stability according to claim 1, characterized in that: In the step S10, the aluminum electrode is sprayed with a thickness of 0.08-0.15 mm, and the insulating glaze coating is coated with a thickness of 0.15-0.3 mm.
Citation Information
Patent Citations
Zinc oxide resistance piece and preparation method thereof
CN101714439A
A method for producing a ZnO Varistor
EP0594120A2